Thermal Performance of Various Roof Elements Under Different Weather Conditions - Joshi, Vijesh Vasanth (2018)
Beside the point of whether the country is developed or underdeveloped, energy crisis is a common scene all over the world. In order to balance energy supply and demand, either one has to increase the supply or decrease the demand. The latter seems to be the better choice since we have limited sources of energy. About 20% - 40% of energy produced by a country is being consumed by HVACs in buildings. Hence much e ort is towards energy conservation in buildings. Around 30% of the building energy consumption in India is due to cooling load. Previous studies have shown that around 60% of the heat due to solar radiation enters through the roof of the building. The present work aims to reduce the heat load entering through the roof by coming up with a better roofing technique for moderate climatic regions. In the present work, enclosures with the side walls and the floor (bottom slab) insulated has been studied both numerically and experimentally. Heat transfer between the ambient and enclosure is only through the roof (top slab). Six common roofing types have been studied in this thesis. Reinforced cement concrete (RCC) roof Mangalore tile roof Thatched roof GI Sheet roof and Concrete roof with lawn (green roof) Concrete roof with a layer of wet sand The experimental studies have been carried out to understand heat transfer through these roofs. A comparative study of all six types of roofs has been done. Apart from this, the effect of a shade net on room models with bare RCC roof and GI sheet roof is also studied and presented in this thesis. Each enclosure has a height of 0.3m and the sides are 1m in size. Mangalore tile and thatched roofs are inclined to the horizontal. To understand the heat flow process, the temperature variations of different surfaces and enclosure air, and, air temperatures near the top and bottom slabs were recorded. In addition, weather conditions such as solar radiation, ambient air temperature, and wind speed are recorded. The details of the experimental set up are given in chapter 3. In chapter 2, a mathematical model to determine the temperature variations in the enclosure is given. All the three modes of heat transfer (conduction, convection and radiation) are present and the system is unsteady. The objective is to find the temperatures of the walls and the enclosure air temperature. Heat flows either from surroundings to the enclosure or from enclosure to the surroundings through the walls of the enclosure. As the solar radiation data is known for a given location, un-steady heat conduction equation is solved for the walls of the enclosure with heat flux boundary conditions to solve for the temperatures. Standard correlations have been used for calculating the convective heat transfer to the ambient and in the enclosure. Most importantly, the experiments conducted were field experiments. The main objective of the study had been to understand the effect of roof on thermal comfort conditions inside the scaled model rooms under five different weather conditions which are commonly observed in warm tropics: (1)summer, (2)winter, (3)cloudy, (4)unsteady, and, (5)rainy. The details of weather conditions have been discussed in chapter 4. In the present analysis, various issues were looked upon such as, temperature values, time lag, thermo-physical properties of the roof material, weather conditions, average over a 24 hours cycle etc. For the comparative analysis, bare RCC roof has been assumed to the base case as most of the buildings are built with RCC roof (for example, in India, around 29% of the buildings have RCC roof, as per 2011 census). On one side we have passive cooling techniques (lawn over RCC roof and wet sand over RCC roof), and, on the other side we have breathing roofs (Mangalore tile roof and thatched roof). Apart from these, the GI sheet roof is commonly used for small scale industries and residential houses. It has been observed that the concrete roof with lawn (hereafter called as lawn over RCC roof ) being the best one among the considered six roofs. Having lawn over RCC roof could result reduction in both solar gain and the diurnal variation of enclosure inside temperatures. The range of temperature variation was least disturbed due to change in weather conditions. In the case of wet sand over RCC roof, the diurnal variations of enclosure inside temperatures were relatively higher as compared with those in the lawn over RCC roof case. As far as breathing roofs are concerned, the two were found to be better than bare RCC roof with thermal comfort as point of view. On the other hand, breathing effects are found to be better in case of Mangalore tile roof than in case of thatched roof. GI sheet roof was found to be the worst among considered for thermal comfort. The effect of using shade net over RCC and GI sheet roof proves to have good potential to reduce cooling load with negligible adverse effects during night time. Detailed discussion of results has been done in chapter 4. Numerical simulations have been carried out for the case of model room with bare RCC roof. A comparative analysis of both experimental and numerical results has been discussed in chapter 5. The important conclusions are discussed in chapter 6.